(untitled) (Interdisciplinary Research in Education, 2024)
Occupational health (OH) is the area of public health that promotes and maintains workers’ highest degree of physical, mental, and social well-being in all occupations. WHO Promotes OH practices that include all three dimensions of health, including physical, mental, and social well-being. Promotive practice is any positive behavioral phenomenon that supports occupational workers, i.e., teachers, carpenters, garment factory workers, cashiers, salespeople, and farmers. To promote OH, there are positive practices of physical well-being, i.e., proper physical exercise, body movement, and a balanced diet. Mental well-being, i.e. yoga, meditation. Social well-being, i.e. social activity, community participation, social meetings, and participation in social functions or events in occupational settings. This study examines the knowledge and promotive practices of OH among secondary-level teachers in Tarkeshwor municipality. The descriptive cross-sectional study included 239 participants from government and private schools. Gender and the state of advertising practices are significantly correlated. Provide mentoring programs and peer support groups so that female educators who actively engage in promotional activities may guide and assist their male counterparts. For all instructors, this can contribute to the development of a welcoming and supportive culture for health promotion.